XENON - Aprile, E. (2007)
The XENON experiment aims at the direct detection of dark matter in the form of WIMPs (Weakly Interacting Massive Particles) via their elastic scattering off Xenon nuclei. With 1 ton of LXe distributed in ten identical modules, the proposed XENON1T experiment will achieve a sensitivity more than a factor of thousand beyond current limits.The detectors are time projection chambers operated in dual (liquid/gas) phase, to detect simultaneously the ionization, through secondary scintillation in the gas, and primary scintillation in the liquid produced by low energy recoils. We review some of the results from the prototype XENON3 detector and briefly discuss about the status of current XENON10 at Gran Sasso Laboratory in Italy.